Altered plasma fibrin clot properties in essential thrombocythemia. (17th February 2016) - Małecki, Rafał; Gacka, Małgorzata; Kuliszkiewicz-Janus, Małgorzata; Jakobsche-Policht, Urszula; Kwiatkowski, Jacek; Adamiec, Rajmund; Undas, Anetta
Abstract: Patients with increased thromboembolic risk tend to form denser fibrin clots which are relatively resistant to lysis. We sought to investigate whether essential thrombocythemia (ET) is associated with altered fibrin clot properties in plasma. Ex vivo plasma fibrin clot permeability coefficient ( K s ), turbidimetry and clot lysis time (CLT) were measured in 43 consecutive patients with ET (platelet count from 245 to 991 × 10 3 /µL) and 50 control subjects matched for age, sex and comorbidities. Fibrinolysis proteins and inhibitors together with platelet activation markers were determined. Reduced K s (−38%, p  < 0.0001) and prolonged CLT (+34%, p  < 0.0001) were observed in ET. The differences remained significant after adjustment for fibrinogen and platelet count. ET was associated with a slightly shorter lag phase (−5%, p  = 0.01) and higher maximum absorbency of the turbidimetric curve (+6%, p  < 0.001). The ET patients had higher plasma P-selectin by 193% ( p  < 0.00001) and platelet factor 4 (PF4) by 173% ( p  < 0.00001), with higher P-selectin observed in 19 (44%) patients with JAK-2 gene V617F mutation. Higher t-PA (+20%, p  < 0.001), 23% higher plasminogen activator inhibitor-1, PAI-1 (+23%, p  < 0.01) and unaltered thrombin-activatable fibrinolysis inhibitor, plasminogen and α2-antiplasmin activity were found in the ET group. K s inversely correlated with fibrinogen, PF4 and C-reactive protein. CLT positively correlated only with PAI-1. Patients with ET display prothrombotic plasma fibrin clot phenotype including impaired fibrinolysis, which represents a new prothrombotic mechanism in this disease.